Explaining Hedge Fund Investment Styles by Loss Aversion - Arjen Siegmann; André Lucas (Tinbergen Institute, 2002)
Recent research reveals that hedge fund returns exhibit a range of different,possibly non-linear pay-off patterns. It is difficult to qualify all these patternssimultaneously as being rational in a traditional framework for optimal financial decisionmaking. In this paper we present a simple model based on loss aversion that can accommodatefor all of these pay-off structures in one unifying framework. We provide evidence thatloss-aversion is a likely assumption for management as well as investor preferences.Following the current empirical literature, we solve a static asset allocation problem thatincludes a nonlinear instrument. We show analytically that four different pay-off functionsmay be rationally optimal. The key parameter in determining which of these four to choosein a specific setting, is the financial planner's surplus. The notion of surplus connectshedge fund manager's incentive schemes with the idea of mental accounting as proposed inrecent behavioral finance research.
Keywords: G11; G23; 330; hedge funds; performance measurement; loss aversion; behavioral finance; Investmentfonds; Hedging; Kapitaleinkommen; Anlageverhalten; Risikoaversion; Finanzanalyse; Theorie; Hedgefonds